2022
DOI: 10.1088/1742-6596/2285/1/012034
|View full text |Cite
|
Sign up to set email alerts
|

The effect of solvents on the morphology of NTO crystal by molecular dynamics

Abstract: In this paper, a molecular model for adsorption of NTO surface-solvent was constructed, and the effects of different solvents on the morphology of NTO crystal were simulated by molecular dynamics. The selected solvents included ethanol, water, acetone, N-methylpyrrolidone (NMP), ethyl acetate and N,N-dimethylformamide. Pure solvents and two co-solvents including NMP/water and ethanol/water were studied to provide theoretical guidance for the selection of solvent systems for NTO recrystallization. In pure solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…In recent years, the application of morphology prediction models, such as the MAE models, , growth mechanistic model, , and dynamic Monte Carlo simulation method, has become increasing popular. Morphology prediction models have been also widely applied in energetic crystals grown under various conditions, such as vacuum, solvents, and additives, with effects of temperature, volume ratio of mixed solvents, supersaturation, and other conditions covered. Also, this research revealed the growth mechanism of energetic crystals at the microscopic level, which presented theoretical guidance for morphology control. Meanwhile, valid force fields are important for the specified energetic compounds.…”
Section: Application Of Morphology Prediction Methods In Energetic Cr...mentioning
confidence: 99%
“…In recent years, the application of morphology prediction models, such as the MAE models, , growth mechanistic model, , and dynamic Monte Carlo simulation method, has become increasing popular. Morphology prediction models have been also widely applied in energetic crystals grown under various conditions, such as vacuum, solvents, and additives, with effects of temperature, volume ratio of mixed solvents, supersaturation, and other conditions covered. Also, this research revealed the growth mechanism of energetic crystals at the microscopic level, which presented theoretical guidance for morphology control. Meanwhile, valid force fields are important for the specified energetic compounds.…”
Section: Application Of Morphology Prediction Methods In Energetic Cr...mentioning
confidence: 99%
“…The thickness of the growth slice in a vacuum is definite, while in a solution, the thickness of the solvent layer in the crystal-solvent interface is uncertain. Since the influence of the adsorption of solvent molecules at the crystal face on crystal growth is not considered in the AE model, the attachment energy is usually modified (E mod ), and the modified attachment energy (MAE) model is derived as Equation ( 6) [31][32][33].…”
Section: Ae and Mae Modelmentioning
confidence: 99%